Activation of Innate Immunity by Bacterial Ligands of Toll-Like Receptors - Akhmatova, Nelli K.; Egorova, Nadezhda B.; Kurbatova, Ekaterina A.; Akhmatov, Elvin A. (Frontiers in Immunology, 2014)
Tγδ and B1 lymphocytes are essential components of the mucosal immune system, activating different bacterial and viral ligands without costimulatory signals and preprocessing of other immune effectors. This ability enables the immune system to provide rapid protection against pathogens and contributes to the decoding mechanism of the sensitizing activity of mucosal antigens, because the interaction of these cells produces antibodies for immunoglobulin M (IgM) and IgA, but not for IgE. We studied 3 routes of introducing antigens for opportunistic microorganisms to activate Tγδ and B1 lymphocytes: subcutaneous, intranasal, and oral. The subcutaneous and intranasal routes produced a significant increase of these cells in lymph nodes associated with the nasal cavity (NALT) and in those associated with bronchial tissue (BALT). The oral route significantly increased levels of these cells in the spleen, in NALT, BALT, and in nodes associated with the gut (GALT). We found that mucosal application of the immunomodulator Immunovac-VP-4 (contains antigens of conditionally pathogenic microorganisms), in conjunction with the activation of Tγδ and B1, induces adaptive immune mechanisms not only in the lymphoid formations associated with the respiratory system and with GALT, but also in the spleen (increased expression of cluster of differentiation 3 [CD3], CD4, CD8, CD19, and CD25). This indicates that there is migration of lymphoid cells from the regional lymph nodes and mucosal lymphoid tissues via the lymph and blood to distant organs, lymphoid development, and both local and systemic immunity. Mucosal application of Immunovac-VP-4 in mice potentiates the cytotoxic activity of NK cells in the NALT, BALT and GALT. The highest cytotoxicity was observed in cells, derived from lymphoid tissue of the intestine after oral immunization. Although we found that cytokine production was increased by all 3 immunization routes, it was most intensive after subcutaneous injection.